(untitled) (Latakia University Journal -Basic Sciences Series, 2013)
في هذاالبحث نبرهن على نتائج جديدة حول ترابط المعطيات للتكراريات ( ( (8) , CR , Suantaiعند تطبيق المؤثرات شبه المقلصة والمعرفةعلى فضاءآت باناخ الحقيقية . نستخدم هذه النتائج لإيجاد النقطة الثابتة لمؤثرمحدددون القيام بحسابها.حيث نقرب هذا المؤثر بأخر شبه مقلص والذي يمكن حساب نقطته الثابتة بوساطة هذه التكراريات . أخيراً نحل مثالين باستخدام برنامج إكسيل لتوضيح النتائج . In this paper we prove new results about data dependence of ( Suantai , CR , (8) ) Iterations when applied to contractive- Like operators in real Banach spaces . We use these results for finding fixed point of certain operator instead of computing. Where we approximate the operator with a contractive –Like one, for which it is possible to compute the fixed point. We resolve two examples by using Excel program to explain the results.